2004
DOI: 10.4049/jimmunol.172.5.2953
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Role for CD37 in T Cell Proliferation

Abstract: CD37 is a leukocyte-specific protein belonging to the tetraspanin superfamily. Previously thought to be predominantly a B cell molecule, CD37 is shown in this study to regulate T cell proliferation. CD37-deficient (CD37−/−) T cells were notably hyperproliferative in MLR, in response to Con A, or CD3-TCR engagement particularly in the absence of CD28 costimulation. Hyperproliferation was not due to differences in memory to naive T cell ratios in CD37−/− mice, apoptosis, or TCR down-modulation. Division cycle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 42 publications
4
89
0
Order By: Relevance
“…45 It is surprising that mice defective for the tetraspanin CD151, which also directly associates with a3b1 and a6b1 integrin, show normal fertility but decreased blood coagulation and hyperproliferative T lymphocytes. 43 This latter phenotype can also be observed in knockout mice for the tetraspanins CD37, 48 Tssc6 49 and CD81. 50 Taken together, these published results suggest that tetraspanin family members can have complementary or partially overlapping roles in different physiological processes or that they merely facilitate physiological processes by enabling the interaction between essential protein components.…”
Section: Discussionmentioning
confidence: 88%
“…45 It is surprising that mice defective for the tetraspanin CD151, which also directly associates with a3b1 and a6b1 integrin, show normal fertility but decreased blood coagulation and hyperproliferative T lymphocytes. 43 This latter phenotype can also be observed in knockout mice for the tetraspanins CD37, 48 Tssc6 49 and CD81. 50 Taken together, these published results suggest that tetraspanin family members can have complementary or partially overlapping roles in different physiological processes or that they merely facilitate physiological processes by enabling the interaction between essential protein components.…”
Section: Discussionmentioning
confidence: 88%
“…Overexpression of the Pointed-P1 transcript induced a significant increase in plasmatocyte numbers, whereas overexpression of a constitutive active form of the inhibitor Anterior open induces lamellocyte formation. Interestingly, in mice, knocking down tetraspanins has been shown to induce lymphocyte proliferation (22). Sinenko et al (23) showed that in Drosophila loss of at least one tetraspanin, tetraspanin68c (tsp68c), was sufficient to induce overproliferation of larval hemocytes.…”
Section: Hemopoiesis and Cell Differentiationmentioning
confidence: 99%
“…Moreover, CD37 is a target for novel immunotherapies to treat B cell malignancies (12)(13)(14)(15)(16)(17)(18). CD37 has also been shown to control functions in T cells and dendritic cells (19)(20)(21)(22). Notably, we recently demonstrated that CD37 promotes migration of dendritic cells (23).…”
mentioning
confidence: 99%